ANALISIS STRATEGI KOMUNIKASI ASERTIF DAN EMPATIK DALAM PENYELESAIAN KONFLIK DI LINGKUNGAN KERJA KULINER - Hilde Febi Annisa Nuryanto; Siska Amelia Maldin (Puslitabmas Batam Tourism Polytecnic, 2026)
Conflict in the culinary work environment is a common phenomenon, primarily due to high work pressure, intensive interpersonal interactions, and the diversity of personal backgrounds and values among employees. This study aims to analyze assertive and empathic communication strategies in resolving conflicts that occur within culinary workplaces. Using a descriptive qualitative approach based on literature review from various journals and scientific articles, the study finds that assertive and empathic communication significantly contributes to constructive conflict resolution. Open two-way communication and the ability to listen actively are identified as key factors in effective conflict management within this sector.